Wewenang KPPU terhadap Pemberian Sanksi pada Pihak Lain Dalam Kasus Persekongkolan Tender - Nurul Fitriani (Universitas Batanghari Jambi, 2021)
Unfair business competition will cause losses to consumers and business parties, unhealthy business practices will also damage national economic stability, which can lead to a monetary crisis in a country. The raise of Regulation Number 5 of 1999 is an effort to prevent unfair business competition practices, especially in organizing tenders for the procurement of goods and / or services. So it is very interesting that the problem in this research is that it takes a juridical approach to cases of tender conspiracy and the authority of the KPPU in imposing sanctions on parties who commit fraudulent efforts in holding tenders, and related to the problem of the absence of sanctions for other parties, namely the committee / tender organizer or government officials and politicians. involved in tender rigging. This study uses the juridical normative research method using secondary data sources through literature studies which are analyzed qualitatively descriptive. The research found that conspiracy in the holding of tenders can occur horizontally or vertically, so that the juridical approach in this case is very suitable to be used to ensnare unhealthy business actors, the juridical approach used is the per se illegal approach. Law Number 5 of 1999 has given the authority to KPPU to impose sanctions on perpetrators of unhealthy business practices, decisions issued by KPPU are legal decisions, however KPPU has the authority to impose sanctions on business practice actors. unhealthy is only limited to administrative sanctions.